Analisis Simulator Kapal STSTC Sebagai Sarana Pembelajaran Utama Di AMY - Yudhi Setiyantara; Bambang Soedijono; Eko Pramono (Sekolah Tinggi Maritim Yogyakarta, 2018)
On October 8th, 2016, it was inaugurated a simulator laboratory of STSTC (Scientific and Technical Simulator Training Center) owned by AMY (Yogyakarta Maritime Academy). The problem of the acceptance and satisfaction level of Nautical cadets to the simulator laboratory as the main learning media can be observed by a study based on Technology Acceptance Model (TAM). Research conducted to get the core problems that caused lack of motivation and satisfaction of Nautical cadets to the existing simulator laboratory. Items for measuring usefulness and ease of use are taken from Davis F.D (1989). Items for measuring user satisfaction are taken from Doll and Torkzadeh (1988). All these variables are measured by Likert scale. The results show that generally the acceptance of Nauticalcadets to the STSTC laboratory simulator especially the simulator bridge is good enough, but could not reach the maximum score caused by relatively low score on the satisfaction value.